Draft Annual Plan 1993-94 Andhra Pradesh Volume-II (Sectoral Programmes) 4. Energy, Science, Technology and Environment - Government of Andhra Pradesh (Government of Andhra Pradesh, 1992)
The Annual Plan 1993-94 for Andhra Pradesh presents an integrated strategy for advancing energy production, science and technology, and environmental sustainability. The plan prioritizes energy infrastructure to meet growing industrial and agricultural demands, highlighting major projects such as the Srisailam Hydro Electric Project (770 MW), Rayalaseema TPS (420 MW), Vijayawada TPS (210 MW), and various mini hydel and wind farm initiatives, collectively addressing projected shortfalls in energy supply. Ongoing projects like the Nagarjuna Sagar and Upper Sileru HES (Stage II) underscore the state’s commitment to expanding capacity, while financial allocations reflect a substantial increase in investment for energy development. Environmental programs focus on pollution mitigation, river cleaning initiatives along the Krishna-Godavari basin, and the establishment of common effluent treatment plants in industrial regions to enhance ecological preservation. Complementing infrastructure goals, the plan emphasizes science and technology development through the AP State Council of Science & Technology (APCOST) and the Rajiv Gandhi Technology Mission, promoting research, community engagement, and renewable energy adoption. With a total proposed outlay of Rs. 860 crores, including Rs. 729.57 crores for the Andhra Pradesh State Electricity Board and Rs. 125 lakhs for environmental initiatives, the plan reflects a comprehensive approach to sustainable development, addressing both socio-environmental concerns and the state’s long-term economic growth objectives.
Finance and Planning (Plg. Wing) Department Government of Andhra Pradesh, Hyderabad December 1992
Finance and Planning (Plg. Wing) Department Government of Andhra Pradesh, Hyderabad December 1992
Keywords: Andhra Pradesh; State Plan; Energy Sector; Srisailam Hydro Electric Project; Rayalaseema TPS; Renewable Energy; Environmental Sustainability; Krishna-Godavari River; Common Effluent Treatment; Science and Technology; APCOST; Rajiv Gandhi Technology Mission